Bus route design with limited travel time - Kuo, Yiyo; Luo, Chi-Ming; Wang, Chi-Chang (Transport, 2013)
Routing problems are especially important for public transport and especially for urban transport. This research deals with designing a bus route to satisfy the demands of most passengers within a limited total bus travel time. A Simulated Annealing (SA) algorithm is proposed for optimizing the routing design. Before applying the proposed SA algorithm, the Taguchi method is adopted for optimizing the setting of parameters. The experimental results show that the proposed SA algorithm with the optimal parameters setting results in better routes than those designed by other research methods. First Published Online: 24 Dec 2013